Fetal 3D cardiovascular cine image acquisition using radial sampling and compressed sensing. Issue 2 (25th September 2022) - Piek, Marjolein; Ryd, Daniel; Töger, Johannes; Testud, Frederik; Hedström, Erik; Aletras, Anthony H.
Abstract : Purpose: To explore a fetal 3D cardiovascular cine acquisition using a radial image acquisition and compressed‐sensing reconstruction and compare image quality and scan time with conventional multislice 2D imaging. Methods: Volumetric fetal cardiac data were acquired in 26 volunteers using a radial 3D balanced SSFP pulse sequence. Cardiac gating was performed using a Doppler ultrasound device. Images were reconstructed using a parallel‐imaging and compressed‐sensing algorithm. Multiplanar reformatting to standard cardiac views was performed before image analysis. Clinical 2D images were used for comparison. Qualitative and quantitative image evaluation were performed by two experienced observers (scale: 1–4). Volumes, mass, and function were assessed. Results: Average scan time for the 3D imaging was 6 min, including one localizer. A 2D imaging stack covering the entire heart including localizer sequences took at least 6.5 min, depending on planning complexity. The 3D acquisition was successful in 7 of 26 subjects (27%). Overall image contrast and perceived resolution were lower in the 3D images. Nonetheless, the 3D images had, on average, a moderate cardiac diagnostic quality (median [range]: 3 [1–4]). Standard clinical 2D acquisitions had a high cardiac diagnostic quality (median [range]: 4 [3, 4]). Cardiac measurements were not different between 2D and 3D images (all p  > 0.16). Conclusion: The presented free‐breathing whole‐heart fetal 3D radial cine MRI acquisition and reconstruction method enables retrospective visualization of all cardiac views while keeping examination times short. This proof‐of‐concept work produced images with diagnostic quality, while at the same time reducing the planning complexity to a single localizer.